"A post-anthropocentric politics: Can neo-materialist theory provide effective solutions to the problems of global mining?". Issue 4 (December 2021) - LeCain, Timothy James
Highlights: Immaterialism of current approaches to global mineral and environmental inequities are inadequate New materialist and post-anthropocentric approaches offer a radical solution Nations with high levels of mineral affluence must share their mineral abundance with the wider globe High levels of consumerism do not generate widespread societal well-being The attendant sacrifice of mineral wealth can be offset by a focus on the authentic material roots of human happiness Abstract: Even more than the Latourian theory that inspired them, neo-materialist and post-anthropocentric theories have sought to shift history's long-standing focus on human beings towards other organisms and things. These new theories argue for a fundamental reorientation of our understanding of culture—and thus society, economics, politics, etc.—to emphasize the inescapable materiality of all aspects of human existence. This is most easily demonstrated through the human alliances with other biological organisms, yet it is no less the case with abiotic materials such as the minerals and metals we extract from the earth's thin veneer of crust. In this paper, I suggest some of the many ways in which human culture and history have emerged from the mining and processing of minerals and their associated pollutants. But I also seek to squarely engage the oft-raised criticism that neo-materialist and post-anthropocentric theories fail to offer a politics or economic theory adequate to dealing with the many challenges humans now face. I argue that these theories can indeed offer just such a politics. However, they require such a radical post-anthropocentric shift away from conventional modernist thinking on both the left and right that some may dismiss them as chimerical. Given the gravity of the challenges we face, however, I argue that it is the contemporary faith in modernist solutions that is truly chimerical. Despite its radical nature, post-anthropocentrism may thus offer a more practical and realistic way forward.